A Shot That Hits the Tumor: Incidental Finding of Early Colon Cancer in a Gunshot Wound Specimen—The Role of Pathologic Examination. (15th April 2019) - Soleimani, Neda; Pakbaz, Sara
Abstract : This report presents incidental finding of early colorectal cancer in an adult patient with gunshot injury. The patient was a 41 y/o man, transferred to our center due to gunshot wound to his abdomen and back. A well differentiated adenocarcinoma, stage I, was incidentally identified during pathologic examination on his segmental proctectomy specimen. This singular case highlights the necessity of caring for all removed tissues, indicating how important they are for both clinicians and pathologists.